The study of Ni-Sn transient liquid phase bonded joints under high temperatures - Yan, Guangxu (2023)
To develop new electronic packaging techniques for harsh environments, the microstructure and associated mechanical properties of Ni-Sn transient liquid phase (TLP) bonded joints at high temperatures have been investigated in this work. The effect of bonding temperature (from 400 °C to 700 °C) on the microstructure and mechanical properties of joints has been studied. In addition, the growth kinetics of Ni3Sn2 and Ni3Sn intermetallic compounds (IMCs) have been studied to analyse the phase transformation mechanisms and microstructure evolution of joints bonded at 500 °C for different times. Also, the long-term (up to 100 h) high-temperature (500 °C) thermal reliability of the joints has been investigated. The results showed that the average shear strength increased as the bonding temperature increased from 400 °C to 500 °C, but continuously dropped as the bonding temperature further increased from 500 °C to 700 °C. It was found that volume diffusion dominated the growth mechanisms of both Ni3Sn2 and Ni3Sn IMCs during bonding at 500 °C for different times. Furthermore, as the aging (at 500 °C) time increased from 0 h to 100 h, the average shear strength of joints continuously decreased. The joints aged for 50 h shear fractured mainly within the Ni3Sn2 IMCs, while the joints after aging for 100 h fractured mainly through the Ni3Sn IMCs.